PENINGKATAN KETERAMPILAN PSIKOMOTOR MELALUI PENERAPAN DISCOVERY LEARNING PADA MATERI FLUIDA STATIS DIKELAS XI IPA SMA YLPI PEKANBARU - Andri, Juki; Zulhelmi, Zulhelmi; Nor, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Psychomotor skills are skills needed to acquire, develop, and apply concepts, laws, and theories of science, both in the form ofmental skills, physical skills (manual) and social skills. This study aims to determine the increase in learning outcomes of students' psychomotor skills after the application of Discovery Learning on the material of the Static Fluda class XI IPA YLPI Pekanbaru. This type of research is a Pre-Experimental design with Intact Group Comparison. This research instrument uses psychomotor sheets by observing students doing practicum using psychomotor assessment sheets on students. Data was collected by providingpsychomotor skills tests to the subject. Data were analyzed descriptively to provide a description of the learning outcomes of students' psychomotor skills including student absorption and learning effectiveness on static fluid material. The results obtained are the average absorption of students that is 88.16% are in the very good category in the experimental class and the average absorption of students that is 73.71% are in the good category in the control class. Thus it can be concluded that the improvement of psychomotor skills through enhancement of psychomotor skills through the application of discovery learning is very effective in knowing the psychomotor skills of students of class XI IPA of YLPI Pekanbaru in static fluid.KeyWords:Discovery Learning Model, Learning Outcomes Of Psychomotor Skills, Static Fluid